O petróleo brasileiro: do nacionalismo à desestatização - GOUVEA, Felipe Allan Ferreira (2022)
The trajectory of oil in Brazil was marked by a dispute over monopolies, in general prevailing state domination. The duality between private and state initiatives, in turn, was built from a nationalist perspective, which presents a history of national sovereignty as the main argument for maintaining the oil sector in the public domain, creating a political and social scenario in which it becomes difficult - and in some ways, unfeasible - to privatize the largest oil exploration, extraction and refining company - Petróleo Brasileiro SA (Petrobrás). The research of the present work has, therefore, as its objective, to draw a historical-social panorama of the nationalist construction on the company, in order to elucidate the difficulties of opening the oil economy to private capital. The methodology used is descriptive-reflective, taking advantage of the bibliographic collection referring to the history of oil in Brazil, so that its explanation allows the results about the impossibilities of privatizing the largest Brazilian oil company.